2016
DOI: 10.1097/sle.0000000000000289
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laparoscopic Lens Contamination in Operating Theaters: A Study on the Frequency and Duration of Lens Contamination and Commonly Utilized Techniques to Maintain Clear Vision

Abstract: Our observational study demonstrates that one third of the duration of a laparoscopic procedure is performed without perfectly clear display. The suboptimal display during an operation is similar to that of driving with a dirty windshield and having to step out of the car to clean it before continuing with the journey. The disruption to operative flow is transcribed as frustration felt by surgeons when display is compromised and having to clean the lens. However, the economical impact of cleaning the lens duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…For a typical laparoscopic operation with four ports, this translates to the same volume as 4 two-liter bottles of soda, potentially containing aerosolized contaminants, being released into the OR environment from the patient’s surgical cavity. Instrument insertion and removal events (conservatively estimated at 6 events/h in the OR) appear to release additional potentially harmful gas volumes equal to 1–2 cans of twelve ounce sodas [ 43 ]. Using an average of 6 instrument removals per hour, results from this study might then suggest a range of 324–684 mL of potentially contaminated gases released during 1 h of surgery (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For a typical laparoscopic operation with four ports, this translates to the same volume as 4 two-liter bottles of soda, potentially containing aerosolized contaminants, being released into the OR environment from the patient’s surgical cavity. Instrument insertion and removal events (conservatively estimated at 6 events/h in the OR) appear to release additional potentially harmful gas volumes equal to 1–2 cans of twelve ounce sodas [ 43 ]. Using an average of 6 instrument removals per hour, results from this study might then suggest a range of 324–684 mL of potentially contaminated gases released during 1 h of surgery (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The Instrument Full Insertion/Removal scenario was used to simulate an instrument exchange or other such removal and/or insertion event, which is commonly experienced during laparoscopy for each and every case. For example, scope removals are often performed to clean the lens, and instruments are commonly removed to achieve access through a different port or to exchange them out for a new instrument [36,37,[40][41][42][43]. Each instrument-port configuration also helped to represent a few different levels of such combinations seen in today's OR.…”
Section: Test Procedures For Each Use Case Scenariomentioning
confidence: 99%
“…Indeed, much of the evidence focussed upon primary outcome measures related to laparoscopic lens fouling or fogging events and thus, failed to consider patient and operative outcomes. Wider research has shown that laparoscopic lens fogging and removal of laparoscopes during surgery can be associated with significant increases in operative time and blood loss, although the effect sizes reported were small and thus, it is not clear whether reductions in lens fogging or fouling would lead to meaningful improvements in operative time and blood loss in routine practice [ 27 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although repeated cleaning of the lens is required during procedures, which is time consuming and distracting, there have been few improvements in lens cleaning methods. Yong et al reported that 37% of operative time was spent under impaired endoscopic views and 7% was used for lens cleaning during endoscopic operations by surgeons [ 1 ]. Moreover, most surgeons are reluctant to clean the lens and sometimes continue the operation with contaminated lens, which is unfavorable from a safety viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…Some commercial devices can provide or maintain a clear endoscopic view [ 3 , 4 ]. In actual practice, however, most of these devices are not commonly used [ 1 ]. Considering this situation, it would be useful to have an alternative method of cleaning the endoscopic lens completely in one short action of a novel device.…”
Section: Introductionmentioning
confidence: 99%